Eating Behaviors: Prevalence, Psychiatric Comorbidity, and Associations With Body Mass Index Among Male and Female Iraq and Afghanistan Veterans. Issue 11 (1st November 2016) - Slane, Jennifer D.; Levine, Michele D.; Borrero, Sonya; Mattocks, Kristin M.; Ozier, Amy D.; Silliker, Norman; Bathulapalli, Harini; Brandt, Cynthia; Haskell, Sally G.
ABSTRACT: Objective: There is a dearth of research examining eating behaviors, such as binge eating, among male and female veterans. The present study evaluated the prevalence of self-reported eating problems as well as associations with body mass index and psychiatric disorders among male and female Iraq and Afghanistan veterans. Methods: Participants were 298 male and 364 female veterans (M = 33.3 ± 10.6 years old) from the Women Veterans Cohort Study, a study of male and female veterans enrolled for Veterans Affairs care in New England or Indiana. Veterans self-reported on emotion- and stress-related eating, eating disorder diagnoses, and disordered eating behaviors. Diagnoses of post-traumatic stress disorder, major depressive disorder, and alcohol abuse were obtained from administrative records. Results: Female veterans reported higher rates of eating problems than did their male counterparts. Women and men who engage in disordered eating had higher rates of post-traumatic stress disorder and major depressive disorder, and women who engage in disordered eating had greater rates of alcohol abuse than did female veterans without eating disordered behaviors. Conclusions: Disordered eating may be a significant issue among Iraq and Afghanistan veterans, and veterans with eating problems are more likely to have comorbid mental health conditions that further increase their health risks.